2017
DOI: 10.1016/j.celrep.2017.01.014
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 Administration Suppresses Retinal and Choroidal Neovascularization in Mice

Abstract: Summary Pathological neovascularization, a leading cause of blindness, is seen in retinopathy of prematurity, diabetic retinopathy and age related macular degeneration. Using a mouse model of hypoxia-driven retinal neovascularization we find that fibroblast growth factor 21 (FGF21) administration suppresses, and FGF21 deficiency worsens, retinal neovessel growth. The protective effect of FGF21 against neovessel growth was abolished in adiponectin (APN)-deficient mice. FGF21 administration also decreased neovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 51 publications
3
48
1
Order By: Relevance
“…We also found that PF-05231023 protection against retinal neuronal deficits was preserved with APN deficiency. In the OIR mouse model of late vasoproliferative retinopathy, FGF21 inhibits pathological neovessel growth mediated by APN (17). Our current findings indicate that FGF21 regulates retinal neuron and neovessel growth through other mechanisms.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…We also found that PF-05231023 protection against retinal neuronal deficits was preserved with APN deficiency. In the OIR mouse model of late vasoproliferative retinopathy, FGF21 inhibits pathological neovessel growth mediated by APN (17). Our current findings indicate that FGF21 regulates retinal neuron and neovessel growth through other mechanisms.…”
Section: Discussionmentioning
confidence: 57%
“…Additionally, PF-05231023induced effect on IL-1b was independent of APN in diabetic retinas, which is in line with the neuronal observation. APN inhibits retinal neovessel growth via tumor necrosis factor-a (TNF-a) (59), and FGF21 also reduces TNF-a in neovascular mouse retinas (17). However, in Akita mice, there was no significant change in retinal Tnfa expression between PF-05231023-and vehicle-treated groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model provided an ideal tool for investigating choroidal capillary sprouting, which was not observed in the animal model in vivo. 22 This effect was also observed when the concentration of hcy was increased to 2 mM, but the sprouting area was not as large as that obtained with 1-mM hcy after 120 hours of culture. Hcy has been reported to be cytotoxic through the upregulation of Fas receptor expression, which leads to cell apoptosis in human umbilical vein endothelial cells cultured with 5-mM hcy.…”
Section: Discussionmentioning
confidence: 77%
“…FGF21 also regulates adiponectin (APN) production and secretion, and APN is key in mediating FGF21 modulation of glucose and lipid metabolism in mice (Holland et al , ; Lin et al , ). FGF21, mediated by APN which is associated with a number of metabolic retinal disorders (Fu et al , 2016), inhibits ocular neovascularization in mice (Fu et al , ). FGF21 also increases APN secretion to diminish accumulation of ceramides in obese animals (Holland et al , ).…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%